Sumbangan Teologis dalam Masyarakat Pancasila - Chang, William (Jurnal Orientasi Baru, 2007)
Theology holds an important role in the life of a nation, culturally, politically and economically. What kind of theology needs to be developed and will better serve the Indonesian society which is multicultural and religiously pluralistic? This article will be focusing on this issue while proposing some ideas on the importance of developing a constructive theology. Constructive theology is an alternative with emphasis on employing a theological method which starts from the real situation of the Indonesian society nowadays, where life, personalty and socially, has been underestimated, dishonored and even destroyed. A constructive theology would help the reorientation of one's mind set, point of view as well as our way of communicating and proceeding to be more inclusive, open and insightful for living our faith.